2017
DOI: 10.1111/gec3.12358
|View full text |Cite
|
Sign up to set email alerts
|

Electric vehicle adoption: An analysis of best practice and pitfalls for policy making from experiences of Europe and the US

Abstract: Accelerating the rate of electric vehicle (EV) adoption is an objective of many countries to mitigate and ameliorate negative externalities arising from the use of fossil fuels for personal motorised transportation including: greenhouse gas (GHG) emissions, air pollution and noise, as well as increasing energy security and reducing budget deficits. Within the dynamic field of EVs, this paper highlights strategic directions for policy makers to increase EV uptake. The paper critically reviews measures adopted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Prior research revealed that most consumers lack adequate, accurate information about EVs [22]; hence, an experimental component was included in the first questionnaire to enhance understanding of the influence that information provision may have on decision making. The methodological framework took into account incentives shown to encourage EV uptake in markets where EVs are more popular (as reported in [2]). This research used a sequential design, as outcomes from the first questionnaire were used to influence design aspects of the second questionnaire [23].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research revealed that most consumers lack adequate, accurate information about EVs [22]; hence, an experimental component was included in the first questionnaire to enhance understanding of the influence that information provision may have on decision making. The methodological framework took into account incentives shown to encourage EV uptake in markets where EVs are more popular (as reported in [2]). This research used a sequential design, as outcomes from the first questionnaire were used to influence design aspects of the second questionnaire [23].…”
Section: Methodsmentioning
confidence: 99%
“…Burning fossil fuels for energy has a pivotal role in global warming, which left unchecked could lead to catastrophic climate change [1]. Not only does oil consumed for transport via internal combustion engine vehicles (ICEVs) result in Greenhouse Gas (GHG) emissions, a wide range of other negative externalities also impact the environment, economy, and society [2]. Transitioning to alternative transport energy sources is critical for Australia to reach its GHG emissions target and reduce its reliance on imported oil; with existing technologies presenting some of the lowest cost options [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of PEV technology is partially reliant on the development of recharging infrastructure, among other constraints (Wolinetz and Axsen, 2017). There are currently only a small number of studies published in the academic literature that review existing research on the development of PEV recharging infrastructure (Broadbent et al, 2017;Hall and Lutsey, 2017). This paper builds on these studies to provide more insights to policymakers and academics.…”
Section: Introductionmentioning
confidence: 99%